Adam Smith, un liberalismo bien temperado - Pfefferkorn, Roland (Sociedad y Economía, 2008)
Due to the huge fortune that has met the Enquiry into the Nature and Causes of the Wealth of Nations, Adam smith is deemed as the “founder father” of political classical economy. A quick reading of his work has sometimes allowed the conversion of this renowned “economist” into a simply liberal thinker, in a partial meaning of this word. The Wealth of Nations, a complex work, deserves a more careful reading. Although Adam Smith is mainly known as political economist, one cannot forget that he taught a subject of moral  philosophy and that he deserved ample acknowledgment for his Theory of Moral Sentiments, where he developed the moral principles that supported many of his economic concepts